ANALISIS EFISIENSI ORGANISASI PENGELOLA ZAKAT NASIONAL DI INDONESIA PERIODE 2016-2018 - Widyowati, Tina (Kasaba, 2021)
Indonesia is a country that has the largest Muslim population in the world, so the potential for zakat is high. Although the potential for zakat in Indonesia is among the largest, the realization of zakat collection that has been captured by members of the Zakat Forum (FOZ) is only 1.8% of the existing potential. Therefore, it is necessary to optimize the potential of zakat, one of which is efficiency. This study aims to determine the level of efficiency of the Zakat Management Organization (OPZ) using the Data Envelopment Analysis (DEA) method. The type of research used in this research is descriptive quantitative research. The sampling technique in this study was purposive sampling, so that data were obtained from each of the financial reports, namely 3 samples of the National Zakat Management Organization in 2016-2018. There are three input variables, namely: Personnel Costs, Socialization Costs, Operational Costs and output variables, namely: Collected Funds and Distributed Funds. This study uses a production approach with input orientation and uses three types of measurements, namely overall efficiency, technicality and scale. The results of this study state that out of 9 DMUs, the efficient Zakat Management Organization reaches a value of 100% seen from 3 measurements, namely in total there are 4 DMUs, technically there are 7 DMUs. Meanwhile, viewed on a scale, there are 4 efficient DMUs. The factor causing inefficiency in the National Zakat Management Organization in Indonesia in 2016-2018 is the waste of excessive use of resources or inputs and the achievement of output that is still minimal so that it does not reach the level of efficiency desired by the Zakat Management Organization.